(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
Malaysia made a good start in its space endeavour, and is currently making gradual progress in the space sector. Since 1996, Malaysia has joined countries who operate their own satellites. Later in 2007, Malaysia made a significance leap by sending the nation’s first astronaut into space. In order to ensure its space sector development is progressing and continues to sustain, a policy framework is needed as a guideline for the government. A policy framework that comprises a set of core principles will act as a backbone for the national space policy. This paper reviews the documents that are related to the national space policy from Canada, Australia and Japan. All of the principles in the policies will be reviewed, and the similarity in these principles will then be highlighted. This paper further proposes several principles for Malaysia to consider as part of its policy framework in space sector development.